Does organising matter? Tracing connections to environmental impacts in different housing estates. (4th November 2009) - Brunklaus, Birgit
Much of the research on buildings and the environment is of a technical-economic nature. But so far, this has not led to any great changes in practice. This article brings organising into the research agenda: Does organising matter for the environmental performance of buildings? If so, how? This question is investigated by a comparative analysis based on an empirical approach. Two housing management practices and their buildings' energy and water performances are analysed relative to each other. It is possible to trace energy and water consumption levels to characteristic management styles (e.g., metaphors of 'caring' and 'emergency-driven'). The analysis shows that organising concepts, more specifically, characteristic management styles, matter for the environment.